2015
DOI: 10.1007/s00170-015-6806-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical-aided abrasive flow machining (ECA2FM) process: a hybrid machining process

Abstract: Abrasive flow machining is a fine finishing process, mainly for the finishing of complex internal/external surfaces of metallic parts. Like most of the finishing processes, this process is also a slow process due to low material removal rate. Hybridization of abrasive flow machining process (AFM) with other non-conventional machining (NCM) processes is being explored in the recent times, so as to overcome the main limitation of low material removal in the AFM process and to satisfy the stringent finish/functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…al. [20] developed Electro chemical assisted AFM and remove the surface material by the chemical action. The researcher used this process for cylindrical workpiece.…”
Section: Orbital Afmmentioning
confidence: 99%
“…al. [20] developed Electro chemical assisted AFM and remove the surface material by the chemical action. The researcher used this process for cylindrical workpiece.…”
Section: Orbital Afmmentioning
confidence: 99%
“…During finishing process, polymeric electrolyte abrasive media was forced through the slight inter-electrode opening that resulted in superior flow confliction of the polymer electrolyte media. Brar et al 31 also developed a hybrid form of electrochemical machining (ECM) and AFM process for the fine finishing of internal holes or prismatic respites. Using fabricated electrochemical-aided abrasive flow machining (ECA 2 FM) setup, they achieved higher MR due to the synergetic action of ECM and AFM processes.…”
Section: Developments In Aff Processmentioning
confidence: 99%
“…Dabrowski et al [8] developed electrochemical-assisted AFM for flat surfaces and obtained a significant change in material removal due to the chemical action. Brar et al [9] used this hybrid process for cylindrical surfaces and found 1.5 times improvement in the material removal.…”
Section: Introductionmentioning
confidence: 99%